ANALISIS FIQH MUAMALAH TERHADAP PRAKTIK PENUKARAN UANG DAN TRANSFER MAHASISWA - Siraj, Sirajul; Siraj, Yani (LPPM STAI Muhammadiyah Probolinggo, 2026)
In the rapidly evolving era of digital finance, the boundaries between social assistance and commercial transactions often become blurred, particularly within academic environments. This research investigates the phenomenon of informal cash-to-transfer money exchanges among students at STAI Ali bin Abi Thalib Surabaya. Facilitated through social media and peer interactions, this practice raises critical questions regarding its compliance with ṣarf (currency exchange) principles in Islamic jurisprudence, specifically concerning fairness, value equality, and the prohibition of riba (usury). The study aims to comprehensively describe the mechanisms of these exchanges, assess the students' literacy regarding fiqh al-mu‘āmalah, and analyze the validity of such practices against Islamic legal standards. Employing a qualitative descriptive method with a case study approach, data were collected via in-depth interviews with 12 students, a fiqh lecturer, and the student body president, supported by observational documentation. The findings reveal a significant gap between theoretical knowledge and practical application; many students engage in these transactions viewing them merely as ta’awun (mutual help), unaware of the strict sharf requirements. While some transactions adhere to yadan bi yadin (spot exchange) and mitslan bi mitslin (equal value), others fall into riba nasī’ah due to transfer delays and riba faḍl due to